2018
DOI: 10.1002/cpdd.425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milk or Apple Juice Ingestion on the Pharmacokinetics of Elvitegravir and Cobicistat in Healthy Japanese Male Volunteers: A Randomized, Single‐Dose, Three‐Way Crossover Study

Abstract: Elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (EVG/COBI/FTC/TAF) is specified in its package insert to be taken with food to obtain sufficient exposure of EVG. It has been reported that a nutritional protein-rich drink shows comparable pharmacokinetics (PK) of EVG to those with a standard breakfast. In this study, the PK profiles of EVG and COBI were evaluated by administration of a single dose of EVG/COBI/FTC/TAF, after ingestion of either a nutritional protein-rich drink, milk, or apple juice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For GFJ, the major flavonoid, naringin, is the main constituent involved in the fexofenadine interaction (Bailey et al, 2007). Subsequent studies have found that absorption of other non-or poorly metabolized drugs such as talinolol (Schwarz et al, 2005), celiprolol (Lilja et al, 2003), atenolol (Jeon et al, 2013), aliskiren (Tapaninen et al, 2011) elvitegravir (Yonemura et al, 2018), and levothyroxine (Lilja et al, 2005) are also reduced when taken with fruit juices. The mechanism of fruit juice interactions with nonmetabolized drugs originally focused on OATP1A2 (Dresser et al, 2002), but many investigators are unable to consistently demonstrate that OATP1A2 is expressed in the gastrointestinal tract (Drozdzik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For GFJ, the major flavonoid, naringin, is the main constituent involved in the fexofenadine interaction (Bailey et al, 2007). Subsequent studies have found that absorption of other non-or poorly metabolized drugs such as talinolol (Schwarz et al, 2005), celiprolol (Lilja et al, 2003), atenolol (Jeon et al, 2013), aliskiren (Tapaninen et al, 2011) elvitegravir (Yonemura et al, 2018), and levothyroxine (Lilja et al, 2005) are also reduced when taken with fruit juices. The mechanism of fruit juice interactions with nonmetabolized drugs originally focused on OATP1A2 (Dresser et al, 2002), but many investigators are unable to consistently demonstrate that OATP1A2 is expressed in the gastrointestinal tract (Drozdzik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While nine studies investigated the effects of food or nutrient supplement on ARV pharmacokinetics [ 12 , 14 , 25 , 27 , 32 , 38 , 42 , 43 , 44 ]. The rest of the studies explored the pharmacokinetic interactions between ARV and vitamins or minerals [ 15 , 29 , 34 , 36 , 37 , 40 ], and dietary supplements [ 28 , 31 , 33 , 35 , 39 , 41 ]. Most studies showed non-significant changes in ARV pharmacokinetic parameters when co-administered with meals.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17,18 ] In addition, in relation to DTG and EVG, there have been reports that concomitant intake of foods or food supplements containing calcium and iron ions by healthy volunteers reduced the values of RAL C max and AUC. [ 19,20 ] However, there have been no previous reports of interaction between the integrase inhibitors and polycationic polymer preparations. Considering the pharmacological mechanism of integrase inhibitors, it is possible that the probable mechanism involved in these interactions may result in the inhibition of absorption, which might occur due to binding between the motif present in the molecular structure of the integrase inhibitor that acts on Mg 2+ in the HIV integrase and ammonium cations in the multivalent metal cation preparations and polycationic polymer preparations.…”
Section: Discussionmentioning
confidence: 99%